Production process of high-viscosity protective film for building materials
The high-viscosity protective film prepared by the three-layer coextrusion film blowing machine process combines the use of modified nano silica and carbon black to solve the problem of low mechanical strength of the existing protective film, and achieves the effects of high viscosity, high mechanical strength, high temperature resistance and light resistance. It is suitable for applications in building materials and other fields.
Patent Information
- Application Number
- CN202411428177.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing protective film has low mechanical strength, resulting in insufficient bonding strength and low peeling force, which can easily cause problems such as degumming, which cannot meet the needs of high viscosity and high mechanical strength in the fields of building materials and other fields.
A three-layer coextrusion film blowing machine process is used to prepare a high-viscosity protective film including the surface layer, the core layer and the adhesive layer. The surface raw materials include linear low-density polyethylene, modified nanosilica, magnesium stearate and antioxidants; the core raw materials include linear low-density polyethylene, polyimide, carbon black and modified nanosilica; the adhesive layer raw materials include high-viscosity SEBS thermoplastic elastomers, acrylic adhesives and modified nanosilica. The mechanical strength and weather resistance of the material are improved by the use of modified nanosilicon dioxide and carbon black.
It has achieved a protective film with high viscosity, high mechanical strength, high temperature and light resistance, significantly improving the adhesive strength and peeling force of the protective film, and is suitable for applications in building materials and other fields.
Smart Images

Figure BDA0005082779990000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective films, and in particular relates to a production process of a high-viscosity protective film for building materials. Background Art
[0002] Protective film products are widely used in the fields of home furnishing, building materials, food, medicine, chemical industry, etc. They are used for packaging, storage and transportation of various products and can play a good protective role. Modern requirements for protective films are getting higher and higher, and higher requirements are put forward for the comprehensive performance of protective film products such as self-adhesion, strength, toughness, puncture resistance, hygiene, good appearance and transparency. At present, the protective films on the market often cannot meet the needs of a wider range of applications due to certain performance defects. The preparation of protective films with good comprehensive performance is an urgent need of the modern packaging industry.
[0003] The patent application with publication number CN109251692 A discloses an anti-debonding PE protective film and its preparation process, including a PE protective film body, an adhesive layer and a release film layer, wherein an adhesive layer is provided on one side of the PE protective film body, and a release film layer is covered on one side of the adhesive layer, wherein the adhesive layer is obtained by uniformly coating and drying a modified pressure-sensitive adhesive. In this patent application, the surface of the PE film needs to be corona treated, the process operation is relatively complicated, and the bonding strength between the finally obtained adhesive layer and the inner layer of the PE film is not ideal.
[0004] At present, the inner layer and the adhesive layer of the protective film still have insufficient bonding strength and low peeling force, which easily cause debonding and other problems. Therefore, the development of a high-viscosity and high-mechanical-strength protective film for building materials is of great significance to expanding the convenience of using the protective film. Summary of the invention
[0005] The object of the present invention is to provide a production process of a high-viscosity protective film for building materials to solve the problem of low mechanical strength of the protective film.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A production process of a high-viscosity protective film for building materials comprises the following steps:
[0008] The surface layer raw material, the core layer raw material and the adhesive layer raw material are extruded through a three-layer co-extrusion film blowing machine and cooled to form a high-viscosity protective film for building materials including a surface layer, a core layer and an adhesive layer.
[0009] The surface layer raw materials include, by weight, 60 to 90 parts of linear low-density polyethylene, 3 to 4 parts of modified nano silicon dioxide, 1 to 2 parts of magnesium stearate, 1 to 2 parts of antioxidant 1010, and 9 to 10 parts of ethylene propylene diene terpolymer;
[0010] The core layer raw materials include, by weight, 70 to 80 parts of linear low-density polyethylene, 60 to 90 parts of polyimide, 1 to 5 parts of carbon black and 1 to 10 parts of modified nano-silicon dioxide;
[0011] The adhesive layer raw materials include, by weight, 20 to 30 parts of high-viscosity SEBS thermoplastic elastomer, 5 to 10 parts of acrylic adhesive and 1 to 3 parts of modified nano silicon dioxide.
[0012] Furthermore, the modified nano-silica is prepared by the following steps: 4.8-5g of nano-silica is slowly added to a mixture of 48-50mL of ethanol and 48-50mL of deionized water, 1-1.1g of an aminosilane coupling agent is added, ultrasonically dispersed for 1-1.2h, heated to 75-80°C and stirred for 5-6h, washed with ethanol at 12000rpm / min for 3 times, and dried at 78-80°C for 24-25h to obtain the modified nano-silica.
[0013] Preferably, the aminosilane coupling agent is KH-550.
[0014] Furthermore, the surface layer raw materials are added to the outer layer hopper, the core layer raw materials are added to the middle layer hopper, and the adhesive layer raw materials are added to the inner layer hopper, and each hopper is mixed evenly.
[0015] Furthermore, the density of the linear low-density polyethylene in the surface layer and the core layer is 0.9 to 0.95 g / cm 3 , the melt index is 0.4~0.45g / min.
[0016] Furthermore, the density of the high viscosity SEBS thermoplastic elastomer in the adhesive layer is 0.85-0.9 g / cm 3 , the melt index is 0.35~0.4g / min.
[0017] Furthermore, the temperature of the film blowing machine is set to 150-200°C.
[0018] Beneficial effects of the present invention:
[0019] (1) The nano-silicon dioxide used in the present invention can improve the heat resistance and ozone resistance of the material. After being treated with a surface modifier, the silanol groups on the nano-silicon dioxide and the silanol groups produced by the hydrolysis of the coupling agent condense to form Si-O-Si bonds, thereby improving the mechanical strength. In addition, the modified nano-silicon dioxide provides linear low-density polyethylene with the ability to resist thermal aging. During the thermal aging process, the nanoparticles act as "connection points", reduce the movement of molecular chains in the medium, increase the crystallinity of the nano-composite material, thereby making the structure more compact and hindering oxygen infiltration; and act as "hot spot", increase the thermal conductivity of the nano-composite material, quickly discharge the heat inside the material, and reduce local overheating.
[0020] (2) The carbon black used in the present invention has a high light absorption coefficient and can strongly absorb ultraviolet light and visible light. The irregular shape of carbon black will cause light scattering. The amino groups in the modified nano-silica can react with the carboxyl groups on the surface of carbon black to form amide bonds and ionic bonds, and form hydrogen bonds with oxygen-containing functional groups such as hydroxyl groups on the surface of carbon black, thereby improving the interfacial bonding between carbon black and other materials and improving the dispersibility of carbon black in the material.
[0021] (3) The polyimide used in the present invention has excellent heat resistance and can effectively avoid the problem that carbon black absorbs heat brought by light energy, thereby causing the thermal stability of the material to decrease. At the same time, it also has good tensile strength and toughness. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] This embodiment provides a production process of a high-viscosity protective film for building materials, including a surface layer, a core layer and an adhesive layer, which is prepared by the following steps:
[0025] The first step is to modify the nano-silica. Slowly add 5g of nano-silica to a mixture of 50mL of ethanol and 50mL of deionized water, and add 1g of KH-550. Ultrasonic dispersion for 1h, then heat to 80℃ and stir for 6h. After the reaction is completed, the product is centrifuged at 12000rpm and then washed with ethanol 3 times, and dried at 80℃ for 24h to obtain modified nano-silica.
[0026] In the second step, the raw materials of the high-viscosity protective film were added into the three-layer co-extrusion film blowing machine, and the temperature was set to 200°C;
[0027] Surface layer materials: by weight, add 90 parts of linear low-density polyethylene, 4 parts of modified nano-silicon dioxide, 2 parts of magnesium stearate, 2 parts of antioxidant 1010, and 10 parts of ethylene propylene diene terpolymer into the outer layer hopper. The density of the linear low-density polyethylene in the surface layer is 0.9g / cm 3 , the melt index is 0.4g / min.
[0028] Core layer materials: by weight, add 80 parts of linear low-density polyethylene, 90 parts of polyimide, 5 parts of carbon black and 10 parts of modified nano-silicon dioxide into the middle layer hopper. The density of linear low-density polyethylene in the core layer is 0.9 g / cm 3, the melt index is 0.4g / min.
[0029] Adhesive layer materials: by weight, add 30 parts of high-viscosity SEBS thermoplastic elastomer, 10 parts of acrylic adhesive and 3 parts of modified nano-silicon dioxide into the inner layer hopper. The density of high-viscosity SEBS thermoplastic elastomer in the adhesive layer is 0.85 g / cm 3 , the melt index is 0.35g / min.
[0030] The materials in each hopper are mixed evenly, extruded by a three-layer co-extrusion film blowing machine, and cooled to obtain a high-viscosity protective film.
[0031] The thickness of the surface layer is 20 μm, the thickness of the core layer is 32 μm, and the thickness of the adhesive layer is 12 μm.
[0032] Example 2
[0033] The present embodiment is different from the embodiment 1 in that the "90 parts of linear low-density polyethylene" in the surface layer raw material is changed to "60 parts of linear low-density polyethylene".
[0034] The remaining raw materials and preparation process remain the same as in Example 1.
[0035] Example 3
[0036] The present embodiment is different from the embodiment 1 in that the “90 parts of polyimide” in the core layer raw material is changed to “60 parts of polyimide”.
[0037] The remaining raw materials and preparation process remain the same as in Example 1.
[0038] Example 4
[0039] The present embodiment is different from the embodiment 1 in that the “10 parts of modified nano silicon dioxide” in the core layer raw material is changed to “5 parts of modified nano silicon dioxide”.
[0040] The remaining raw materials and preparation process remain the same as in Example 1.
[0041] Example 5
[0042] The present embodiment is different from the embodiment 1 in that the “30 parts of high-viscosity SEBS thermoplastic elastomer” in the adhesive layer raw material is changed to “20 parts of high-viscosity SEBS thermoplastic elastomer”.
[0043] The remaining raw materials and preparation process remain the same as in Example 1.
[0044] Example 6
[0045] The present embodiment is different from the embodiment 1 in that "the temperature of the film blowing machine is set to 200° C." is changed to "the temperature of the film blowing machine is set to 150° C.".
[0046] The remaining raw materials and preparation process remain the same as in Example 1.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that magnesium stearate and antioxidant 1010 are not added to the surface layer raw materials.
[0049] The remaining raw materials and preparation process remain the same as in Example 1.
[0050] Comparative Example 2
[0051] The difference between this comparative example and Example 1 is that no carbon black is added.
[0052] The remaining raw materials and preparation process remain the same as in Example 1.
[0053] Comparative Example 3
[0054] The difference between this comparative example and Example 1 is that no modified nano-silicon dioxide is added.
[0055] The remaining raw materials and preparation process remain the same as in Example 1.
[0056] Comparative Example 4
[0057] The difference between this comparative example and Example 1 is that KH-550 is not added.
[0058] The remaining raw materials and preparation process remain the same as in Example 1.
[0059] Comparative Example 5
[0060] The difference between this comparative example and Example 1 is that no carbon black and modified nano-silicon dioxide are added to the core layer raw materials.
[0061] The remaining raw materials and preparation process remain the same as in Example 1.
[0062] Comparative Example 6
[0063] The difference between this comparative example and Example 1 is that the coupling agent "KH-550" is replaced by "KH-560".
[0064] The remaining raw materials and preparation process remain the same as in Example 1.
[0065] Comparative Example 7
[0066] The difference between this comparative example and Example 1 is that no high-viscosity SEBS thermoplastic elastomer is added to the adhesive layer raw material.
[0067] The remaining raw materials and preparation process remain the same as in Example 1.
[0068] The performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 7.
[0069] According to GB / T 2792-2014 "Test method for peel strength of adhesive tape", the protective films obtained in various embodiments and comparative examples of the present application were tested for adhesion;
[0070] According to GB / T 32368-2015 "Test method for high temperature and high humidity aging of adhesive tape", the protective films obtained in various embodiments and comparative examples of the present application were tested for high temperature resistance;
[0071] According to GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics", the protective films obtained in various embodiments and comparative examples of the present application were tested for tensile properties;
[0072] According to GB / T 16422.2-2022 "Xenon Arc Lamp Artificial Weathering Test", the protective films obtained in various embodiments and comparative examples of the present application were tested for light resistance;
[0073] According to GB / T 7141-2008 "Test Method for Thermal Aging of Plastics", thermal aging tests were performed on the protective films obtained in various embodiments and comparative examples of the present application;
[0074] The results are shown in Table 1:
[0075] Table 1
[0076]
[0077] It can be seen from Table 1 that, compared with Example 1, Examples 2-6 have different degrees of decline in various aspects, indicating that the ratio of each component and the experimental conditions have an impact on the performance of the protective film.
[0078] Compared with Example 1, Comparative Example 1 mainly shows a decrease in high temperature resistance and tensile strength, because magnesium stearate, as a stabilizer and lubricant, can improve the uniformity and stability of the product, and antioxidant 1010 can prevent the performance degradation, discoloration and degradation of the material caused by oxidation, and maintain the appearance and mechanical properties of the product; Compared with Example 1, Comparative Examples 2-5 show a decrease in tensile strength and light resistance, which shows that the combination of the two can improve the mechanical properties of the protective film, nano-silica can improve the heat resistance and ozone resistance of the material, and carbon black helps to improve weather resistance and UV resistance. By treating the nano-silica with a surface modifier, the mechanical strength is improved while the heat aging resistance of the protective film is improved; compared with Example 1, the comparative example 6 has no amino group in KH-560 and no amide bond is formed, resulting in a decrease in the performance of the protective film; and compared with Example 1, the comparative example 7 has a significantly reduced adhesion after not adding the high-viscosity SEBS thermoplastic elastomer. The high-viscosity SEBS can provide stronger bonding strength and has good weather resistance, and can resist ultraviolet rays, ozone and oxidation, which also explains the reason why the light resistance of comparative example 7 is reduced.
[0079] Compared with Example 1, the thermal aging performance of Comparative Example 3 is significantly reduced, indicating that doping with nano-silica can arrange the polyethylene macromolecular chains regularly, increase the connection between the molecular chains, and improve the density of the structure. Compared with Comparative Example 3, Comparative Example 4 shows stronger resistance to thermal aging, indicating that the modified nano-silica can be evenly dispersed in the material to avoid agglomeration.
[0080] In summary, the present invention provides a production process for a high-viscosity protective film for building materials, which has good adhesion, high temperature resistance, high mechanical strength and good light resistance, and has good application prospects.
[0081] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process of a high-viscosity protective film for building materials, characterized in that: The steps include: The surface layer raw material, the core layer raw material and the adhesive layer raw material are extruded through a three-layer co-extrusion film blowing machine, and cooled to form a high-viscosity protective film for building materials including a surface layer, a core layer and an adhesive layer; The surface layer raw materials include, by weight, 60 to 90 parts of linear low-density polyethylene, 3 to 4 parts of modified nano silicon dioxide, 1 to 2 parts of magnesium stearate, 1 to 2 parts of antioxidant 1010, and 9 to 10 parts of ethylene propylene diene terpolymer; The core layer raw materials include, by weight, 70 to 80 parts of linear low-density polyethylene, 60 to 90 parts of polyimide, 1 to 5 parts of carbon black and 1 to 10 parts of modified nano-silicon dioxide; The adhesive layer raw materials include, by weight, 20 to 30 parts of high-viscosity SEBS thermoplastic elastomer, 5 to 10 parts of acrylic adhesive and 1 to 3 parts of modified nano silicon dioxide.
2. A process for producing a high-viscosity protective film for building materials according to claim 1, characterized in that: The density of linear low-density polyethylene in the surface layer and the core layer is 0.9 to 0.95 g / cm 3 , the melt index is 0.4~0.45g / min.
3. The production process of a high-viscosity protective film for building materials according to claim 1, characterized in that: The density of high viscosity SEBS thermoplastic elastomer in the adhesive layer is 0.85~0.9g / cm 3 , the melt index is 0.35~0.4g / min.
4. The production process of a high-viscosity protective film for building materials according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: slowly adding nano silicon dioxide into a mixture of ethanol and deionized water, adding an aminosilane coupling agent, ultrasonically dispersing, heating and stirring, washing and drying to obtain the modified nano silicon dioxide.
5. A process for producing a high-viscosity protective film for building materials according to claim 4, characterized in that: The aminosilane coupling agent is KH-550.
6. The production process of a high-viscosity protective film for building materials according to claim 1, characterized in that: The film blowing machine temperature is set at 150-200°C.
Citation Information
Patent Citations
Anti-degumming PE protective film, and preparation method thereof
CN109251692A